Pengaruh Reward dan Beban Kerja terhadap Kinerja Tenaga Penjualan melalui Motivasi Kerja: Bukti Empiris dari PT Bank Negara Indonesia (Persero) Tbk Regional Palembang - Agustini Daely; Wita Farla; Yos Karimudin (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of reward and workload on sales performance through the mediating role of work motivation among Sales Generalists at PT Bank Negara Indonesia (Persero) Tbk Regional Palembang. A quantitative approach with a cross-sectional survey was employed involving 117 respondents, consisting of 102 Sales Generalists and 15 team leaders, selected using a census sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that reward has a positive and significant effect on both sales performance and work motivation, whereas workload has a negative and significant effect on both work motivation and sales performance. In addition, work motivation positively influences sales performance and significantly mediates the relationships between reward and sales performance as well as between workload and sales performance. These findings highlight the importance of implementing effective reward systems and balanced workload management to strengthen employees' work motivation and improve sales performance in the banking industry.